Immunohistochemistry and in situ hybridization of human carcinomas - Hayat, M. A., 1940-; ScienceDirect eBooks (Boston : Elsevier Academic Press, 2004)
Classical histology has been augmented by immunohistochemistry (the use of specific antibodies to stain particular molecular species in situ). Immunohistochemistry has allowed the identification of many more cell types than could be visualized by classical histology, particularly in the immune system and among the scattered hormone-secreting cells of the endocrine system. This book discusses all aspects of immunohistochemistry and in situ hybridization technologies and the important role they play in reaching a cancer diagnosis. It provides step-by-step instructions on the methods of additional molecular technologies such as DNA microarrays, and microdissection, along with the benefits and limitations of each method. * The only book available that translates molecular genetics into cancer diagnosis * Methods were developed by internationally-recognized experts and presented in step-by-step manner * Results of each Immunohistochemical and in situ hybridization are presented in the form of color illustrations.
PART I. MOLECULAR GENETICS -- IDENTIFICATION OF TUMOR-SPECIFIC GENES -- THE POSTTRANSLATIONAL PHASE OF GENE EXPRESSION IN TUMOR DIAGNOSIS -- ROLE OF BARD1 IN APOPTOSIS AND CANCER -- ANGIOGENESIS, METASTASIS AND EPIGENETICS IN CANCER -- CAN EFFECTOR CELLS REALLY EFFECT AN ANTITUMOR RESPONSE AS CANCER THERAPY? -- CIRCULATING CANCER CELLS -- CIRCULATING CANCER CELLS: FLOW CYTOMETRY, VIDEO-MICROSCOPY AND CONFOCAL LASER SCANNING MICROSCOPY -- PART 2. GASTROINTESTINAL CARCINOMA -- GASTROINTESTINAL CARCINOMA: AN INTRODUCTION ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF P53 IN GASTRIC CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF p53, Rb, AND p16 PROTEINS IN ANAL SQUAMOUS CELL CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF p53 AND VEGF IN GASTRIC CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF p150 IN -- GASTRIC CARCINOMA: THE ASSOCIATION WITH P53, APOPTOSIS AND CELL PROLIFARATION -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF Ki-67 IN ADENOCARCINOMA OF LARGE INTESTINE -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF KIT/CD117 IN GASTROINTESTINAL STROMAL TUMORS -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF BUB1 PROTEIN IN GASTRIC CANCER -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF EPIDERMAL GROWTH FACTOR IN GASTRIC TUMORS -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF BETA-CATENIN AND MUCIN IN STOMACH CANCER -- LOSS OF CYCLIN D2 EXPRESSION IN GASTRIC CANCER -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF E-CADHERIN DIFFUSE-TYPE GASTRIC CANCER -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF APC AND E-CADHERIN IN GASTRIC CARCINOMA -- IMMUNOHISTOCHEMICAL EXPRESSION OF CHROMOGRANIN A (CgA) AND Leu-7 IN GASTROINTESTINAL CARCINOIDS -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF MUC5B IN GASTRIC CARCINOMA -- ANGIOGENIN IN GASTRIC CANCER AND ITS ROLES IN MALIGNANCY -- ROLE OF HELICOBACTOR PYLORI IN GASTRIC CANCER -- PROTEIN ALTERATIONS IN GASTRIC ADENOCARCINOMA -- VESICLE PROTEINS IN NEUROENDOCRINE AND NONENDOCRINE TUMORS OF THE GASTROINTESTINAL TRACT -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF CASPASE-3 IN GASTRIC CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF PRL-3 PHOSPHATASE IN GASTRIC CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF DNA METHYLTRANSFERASE 1 PROTEIN IN GASTRIC CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF -- CYTOPLASMIC TREFOIL FACTOR FAMILY-2 IN GASTRIC CANCER -- PART 3. OVARIAN CARCINOMA -- OVARIAN CARCINOMA: AN ITNRODUCTION -- METHODS FOR DETECTING GENETIC ABNORMALITIES IN OVARIAN CARCINOMA USING FLUORSCENCE IN SITU HYBRIDIZATION AND IMMUNOHISTOCHEMISTRY -- QUANTITATIVE IMMUNOHISTOCHEMISTRY (Q-IHC) BY -- DETERMINING THE NORM OF THE IMAGE DATA FILE -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF HER2/neu IN HIGH GRADE OVARIAN SEROUS PAPILLARY CANCER -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF BRCA1 IN OVARIAN CARCINOMA -- ROLE OF BRCA/BRCA2 IN OVARIAN, FALLOPIAN TUBE AND PERITONEAL PAPILLARY SEROUS CARCINOMA -- K-RAS MUTATIONS IN SEROUS BORDERLINE TUMORS OF THE OVARY -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF Ki-67 IN OVARIAN CARCINOMA -- THE ROLE OF EXPRESSION OF ESTROGEN RECEPTOR BETA, -- PROLIFERATING CELL NUCLEAR ANTIGEN AND P53 IN OVARIAN GRANULOSA CELL TUMORS -- ROLE OF CYCLOOXYGENASE-2 EXPRESSION -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF -- CYCLOOXYGENASE-2 AND PEROXISOME PROLIFERATOR ACTIVATED-RECEPTOR IN EPITHELIAL OVARAIN TUMORS -- CDX-2 IMMUNOSTAINING IN PRIMARY AND SECONDARY OVARIAN CARCINOMAS -- EPITHELIAL OVARIAN CANCER AND THE E-CADHERIN-CATENIN COMPLEX -- ROLE OF CYTOKERATIN IMMUNOHISTOCHEMISTRY IN THE DIFFERENTIAL DIAGNOSIS OF OVARIAN TUMORS -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF -- CYTOKERATINS AND MUCINS IN AMPULLARY CARCINOMA -- ROLE OF INTEGRINS IN OVARIAN CANCER -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF -- VASCULAR ENDOTHELIAL GROWTH FACTOR C AND VASCULAR ENDOTHELIAL GROWTH FACTOR RECEPTOR 2 IN OVARIAN CANCER -- USE OF MICROARRAY IN IMMUNOHISTOCHEMICAL LOCALIZATION OF SMAD IN OVARIAN CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF FAS IN OVARIAN CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF LEWIS Y ANTIGEN IN OVARIAN CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF ETS-1 FACTOR IN OVARIAN CARCINOMA -- ROLE OF MCL-1 OVARIAN CARCINOMA -- ROLE OF Elf-1 IN EPITHELIAL OVARIAN CARCINOMA: IMMUNOHISTOCHEMISTRY -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF OCT4 IN OVARIAN DYSGERMINOMA -- IMMUNOHISTOCHEMICAL VALIDATION OF B7-H4 (DD-0110) -- AS A BIOMARKER OF OVARIAN CANCER: CORRELATION WITH CA125 -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF ALPHA -- GLUTATHIONE S-TRANSFERASE IN OVARIAN CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF AMINOPEPTIDASES IN OVARIAN CARCINOMA -- EXPRESSIONS OF ANGIOPOIETIN-1, ANGIOPOIETIN-2, AND -- TIE2 IN NORMAL OVARY WITH CORPUS LUTEM AND IN OVARIAN CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF 1,25- -- DIHYDROXYVITAMIN-D3-RECEPTORS IN OVARIAN CARCINOMA -- ROLE OF IMMUNOHISTOCHEMICAL EXPRESSION OF ANTIGENS IN NEUROENDOCRINE CARCINOMA OF THE OVARY AND ITS DIFFERENTIAL DIAGNOSTIC CONSIDERATIONS -- ROLE OF IMMUNOHISTOCHEMISTRY IN ELUCIDATING LUNG CANCER METASTATIC TO THE OVARY FROM PRIMARY OVARIAN CARCINOMA.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Cancer -- Immunodiagnosis; Immunohistochemistry; In situ hybridization; Fluorescence in situ hybridization; Cancer -- Immunodiagnosis; Fluorescence in situ hybridization; Immunohistochemistry; In situ hybridization; Neoplasms -- diagnosis; Situ Hybridization -- methods; Genetic Techniques; Electronic books